2020
DOI: 10.1093/brain/awaa063
|View full text |Cite
|
Sign up to set email alerts
|

Novel congenital disorder of O-linked glycosylation caused by GALNT2 loss of function

Abstract: Congenital disorders of glycosylation are a growing group of rare genetic disorders caused by deficient protein and lipid glycosylation. Here, we report the clinical, biochemical, and molecular features of seven patients from four families with GALNT2-congenital disorder of glycosylation (GALNT2-CDG), an O-linked glycosylation disorder. GALNT2 encodes the Golgi-localized polypeptide N-acetyl-d-galactosamine-transferase 2 isoenzyme. GALNT2 is widely expressed in most cell types and directs initiation of mucin-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 25 publications
4
49
0
Order By: Relevance
“…Cell surface glycans are biosynthesized from 10 monosaccharide units by the combinatorial activity of more than 250 glycosyltransferases (GTs). Although the secretory pathway comprises an arsenal of GTs that influence each other through compensation and competition [ 4 ], deficiencies of individual GTs are related to congenital disorders of glycosylation [ 5 ]. Despite forays made into understanding the molecular details of GT activity, our insights are still limited by the complexity of the secretory pathway and the analytical challenges associated with studying glycans.…”
Section: Introductionmentioning
confidence: 99%
“…Cell surface glycans are biosynthesized from 10 monosaccharide units by the combinatorial activity of more than 250 glycosyltransferases (GTs). Although the secretory pathway comprises an arsenal of GTs that influence each other through compensation and competition [ 4 ], deficiencies of individual GTs are related to congenital disorders of glycosylation [ 5 ]. Despite forays made into understanding the molecular details of GT activity, our insights are still limited by the complexity of the secretory pathway and the analytical challenges associated with studying glycans.…”
Section: Introductionmentioning
confidence: 99%
“…GalNAc-type O-glycosylation is an exceptional form of protein glycosylation in that it is regulated by a large family of up to 20 GalNAc-T isoforms, providing opportunities for a high degree of differential regulation of glycosites on specific proteins in cells 48 . The GalNAc-T isoforms are known to serve co-regulatory roles in fine-tuning functions of specific proteins with clear disease-causing consequences 23,[49][50][51] , and we recently demonstrated that graded induction of individual GalNAc-T isoforms in cell models provides corresponding graded O-glycosylation of highly select glycosite substrates specific to the induced GalNAc-T 52 . In the present study, we did not address the biosynthesis of glycosylated peptide hormones and in particular the specific GalNAc-T isoforms controlling glycosylation of the identified glycosites.…”
Section: Discussionmentioning
confidence: 98%
“…ppGalNAc-T2 has been shown to regulate high-density lipoprotein cholesterol (HDL-C) metabolism by O -glycosylation of phospholipid transfer protein (PLTP) and is suggested to associate with dyslipidemia and coronary artery disease (CAD) [ 40 , 41 ]. Congenital loss of ppGalNAc-T2 function causes low plasma HDL-C levels accompanying mental and growth retardation [ 42 ]. In Drosophila, O -glycosylation regulates the secretion and localization of extracellular matrix proteins involved in proper cell–cell adhesion, leading to wing formation [ 43 ].…”
Section: O -Glycans and Ppgalnac-tmentioning
confidence: 99%